Analisis Terhadap Kesalahan Berbahasa Indonesia Dalam Artikel Yang Membahas Peningkatan Keterampilan Menulis Puisi Melalui Strategi Pikir Plus Dengan Memanfaatkan Media Gambar Peristiwa - Aulia, Citra; Simaremare, Ermas; Kautsar, M. Anas; Lumbangaol, Riski Fanni; Siregar, Risbue; Haza, Suci Amaliah (Invention: Journal Research and Education Studies, 2025)
This research examines linguistic errors found in a scientific article titled Enhancing Poetry Writing Skills through the Pikir Plus Strategy with the Use of Event Image Media. The objective of this study is to identify the types of language errors that occur and propose corrective solutions. A qualitative descriptive method was employed, utilizing document analysis techniques to assess spelling, word choice, grammar, as well as sentence cohesion and coherence. The findings reveal various errors, including non-compliance with the General Guidelines for Indonesian Spelling (PUEBI), improper use of capital letters, punctuation mistakes, and ineffective sentence structures. These errors are caused by several factors, such as limited understanding of linguistic rules, the influence of regional and foreign languages, and minimal attention to academic writing conventions. Therefore, increasing awareness and improving learning regarding the proper use of standard Indonesian are essential to enhance the quality of academic writing.